(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The soluble nutrients are plays vital role in aquatic water bodies. Then micro and macro nutrients both are highly essential in building up of biological life forms. The plankton and nutrient in water bodies have a significant role in setting up the aquatic ecosystem as well as aquatic resources. In the present research study, the occurrence and distribution of phytoplankton from Sudha reservoir from Bhokar tahsil were undertaken for about two years during 2018 to 2019. Rainwater is the main source for surface water; it includes rivers, lakes, ponds, reservoirs, streams, etc. The dam is surrounded by various types of plants and agricultural land with different types of soil. When rainfall occurs the water from surrounding area and agricultural land containing various organic traces enter into the Sudha reservoir. The observed mean values of parameters like pH, Phosphate, Sulphate, Nitrite-nitrogen, Ammonia, Phytoplankton and Zooplankton etc. All the studied parameters are within the permissible limit. The study showed few phytoplanktonic genera and the good population of mainly five genera of phytoplankton and zooplankton each were observed.